Metabolic Flow of C6 Volatile Compounds From LOX-HPL Pathway Based on Airflow During the Post-harvest Process of Oolong Tea - Zhou, Zi-wei; Wu, Qing-yang; Ni, Zi-xin; Hu, Qing-cai; Yang, Yun; Zheng, Yu-cheng; Bi, Wan-jun; Deng, Hui-li; Liu, Zhen-zhang; Ye, Nai-xin; Lai, Zhong-xiong; Sun, Yun (Frontiers in Plant Science, 2021)
Aroma is one of the essential quality indicators of oolong tea. C6 acid and its derivative esters are important components in fatty acid(FA)-derived volatile in oolong tea. However, the formation and regulation mechanism of C6 acid during the post-harvest process of oolong tea remained unclear. To gain better insights into the molecular and biochemical mechanisms behind C6-compounds of oolong tea, a combined analysis of ADH activity, CsADH2 key genes expression and FA-derived metabolome during the psot-harvest process of oolong tea was performed for the first time, complemented with CsHIP (Hypoxia induced protein conserved region) genes expression analysis. VFAD-targeted metabolomics analysis by head-space solid-phase microextraction gas chromatography time-of-flight mass spectrometry (HS-SPEM-GC-TOF MS), (Z)-3-hexen-1-ol content increased after each turn over, while hexanoic acid content showed the opposite trend. Both the activity of ADH and the expression level of CsADH gene in oxygen-deficitt-turnover tea leaves(ODT) were higher than that of oxygen- turnover tea leaves(OT). The C6-alcohol-derived esters content of OT were significantly higher than that of the ODT, but the C6-acid-derived esters content were to the contrary. Moreover, we screened and analyzed the HIP genes family, and found that ODT treatment could significantly promote the up-regulation of CsHIG4 and CsHIG6 gene expression. Our results show that the formation mechanism of oolong tea aroma quality mediated by airflow factor in term of LOX pathway, which provides a theoretical reference for quality control in post-harvest process of oolong tea in the future.